A Synopsize Report of the Various Perspectives of Urolithiasis and its Ethno-Medical Future - Sharma, Sarita; Raval, Amit J.; Koneri, Raju; Sharma, Gaurav Kumar (Journal of Drug Delivery and Therapeutics, 2022)
Kidney stone formation or urolithiasis is a complex process that results from a series of physicochemical events, including supersaturation, nucleation, growth, aggregation, and retention in the kidney. Urolithiasis affects about 10% of people in the Western world in their 70s. Epidemiological data show that calcium oxalate is the major mineral in most kidney stones. To date, great progress has been achieved in identifying metabolic risk factors that predispose to this complex condition, the most prominent of which is hypercalcemia. The unique genetic and epigenetic elements concerned in urolithiasis have remained largely unknown, thanks in part to the candidate gene and linkage techniques that have been available to date, which are inherently low in terms of their decision-making power and ability to assess modest outcomes in complicated traits. However, when combined with studies of rare Mendeliantypes of urolithiasis linked to various metabolic danger factors, those methodologies have shown organic pathways that appear to underpin the improvement of stones in the urinary system. Furthermore, despite substantial improvements in research into the biochemical and physical signs of kidney stones, therapeutic therapy medications are in short supply. Phytotherapy may be effective as an alternative or adjunctive therapy in the treatment of urolithiasis, according to data from in vitro, in vivo, and clinical investigations. This article discusses the various varieties of stones, as well as their characteristics. The varieties of stones, their composition, clinical evaluation, various surgical procedures for removal, treatment downsides, and several herbal medicine details giving therapeutic effects are all included in this review. Keywords: Urolithiasis, Epidemiological data, Diagnosis, Herbal drugs, Ethno medicines.